A New Risk Model Based on 7 Quercetin-Related Target Genes for Predicting the Prognosis of Patients With Lung Adenocarcinoma - Zhang, Yun-Qiang; Li, Kai; Guo, Qiang; Li, Dan (Frontiers in Genetics, 2022)
Background: Studies have reported that quercetin inhibits the growth and migration of lung adenocarcinoma (LUAD). This study aimed to explore the roles and mechanisms of quercetin target genes in the progression of LUAD. Methods: The quercetin structure and potential target genes of quercetin were explored in the Traditional Chinese Medicine Systems Pharmacology and SwissTargetPrediction databases. The differentially expressed quercetin target genes were identified in The Cancer Genome Atlas (TCGA) database, and the clinical values of quercetin target genes were explored. Subsequently, a risk model was constructed via the Cox regression and survival analysis to evaluate the potential effects and possible mechanisms of quercetin target genes. Results: The quercetin differential target genes involved in biological processes such as the oxidation-reduction process, cell proliferation, G2/M transition of the mitotic cell cycle, and were related to the lung cancer. NEK2, TOP2A, PLK1, CA4, CDK5R1, AURKB, and F2 were related to the prognosis, and were independent factors influencing the prognosis of LUAD patients. The risk model was related to the gender, clinical stage, T stage, lymph node metastasis, and survival status of LUAD patients, and was independent risk factor associated with poor prognosis. In the high-risk group, the risk model involved signaling pathways such as cell cycle, DNA replication, spliceosome, and homologous recombination. Conclusion: The quercetin potential target genes NEK2, TOP2A, PLK1, CA4, CDK5R1, AURKB, and F2 were related to the diagnosis and prognosis of LUAD patients. A risk model based on 7 quercetin target genes could be used to assess the prognosis of patients with LUAD.